Energy Analysis and Economy Performance of a Hybrid Solar Dryer for Drying Coffee - Suherman, Suherman; Hadiyanto, Hadiyanto; Franz, Nicholas; Kamandjaja, Vimala; Sinuhaji, Tubagus Rayyan Fitra (Jurnal Sains Materi Indonesia, 2024)
This work studies the effect of the drying temperature on the profile of the water content, drying rate, drying efficiency, economic performance, and the quality of Robusta and Arabica coffee beans using the hybrid solar dryer. The drying instrument with the help of LPG heating is used in this research with a specified temperature of 40 ℃, 50 ℃, and 60 ℃. The research is conducted on a sunny day for 1 day for each temperature and coffee beans. The temperature profile shows that the lowest water content in the study is 60 ℃. The drying rate for both 50 ℃ and 60 ℃ are similar and the highest average efficiency of the instrument is at 50 ℃ for both Robusta and Arabica beans. The dominant peak in GCMS analysis result of coffee samples was caffeine with a total area percentage of 30.89%, the description of the coffee bean structure using SEM test resulted in a hole size of 5-10 µm, the obtained fat content was 1.6%, the obtained protein content 17.3%. A hybrid solar dryer is an environmentally friendly solution that enables faster coffee drying, with a payback period of 1.5 years for both coffee bean types.